Formation of ultra-short-period planet K2-266b via obliquity-driven tidal migration - Deng, Feifan (Nanyang Technological University, 2023)
Ultra-short-period planets (USPs), with orbital periods of less than one day, have been the subject of intense research since their discovery over a decade ago. Their close proximity to their host stars challenge our understanding of planet formation, and offer a valuable opportunity to probe the physical mechanisms that shape planetary systems. In this report, we aim to evaluate the likelihood of K2-266b forming via obliquity-driven tidal migration. N-body tidal simulations of the K2-266 system with all of its confirmed planets were conducted to investigate the spontaneous effects of obliquity tides on K2-266b. We attempted to force the planet into Cassini state 2 through fine-tuning of initial conditions without imposing migration of the planets. Despite incorporating the ideal conditions into the simulations, our results show that K2-266b may be unable to enter Cassini state 2 and tidal dissipation may be insufficient for K2-266b to initiate migration. The obliquity of K2-266b was successfully excited and maintained. However, it is not a product of tidal dissipation and is likely due to gravitational influence from K2-266c. Although the obliquity tides mechanism has no explicit constraint on the mass ratio of the planets, it may not be applicable for USPs such as K2-266b, which are larger than their companion planets.